Molecular topography of an entire nervous system - Taylor, Seth R; Santpere, Gabriel; Weinreb, Alexis; Barrett, Alec; Reilly, Molly B; Xu, Chuan; Varol, Erdem; Oikonomou, Panos; Glenwinkel, Lori; McWhirter, Rebecca; Poff, Abigail; Basavaraju, Manasa; et al. (Cell, 2021)
We have produced gene expression profiles of all 302 neurons of the C. elegans nervous system that match the single-cell resolution of its anatomy and wiring diagram. Our results suggest that individual neuron classes can be solely identified by combinatorial expression of specific gene families. For example, each neuron class expresses distinct codes of ∼23 neuropeptide genes and ∼36 neuropeptide receptors, delineating a complex and expansive "wireless" signaling network. To demonstrate the utility of this comprehensive gene expression catalog, we used computational approaches to (1) identify cis-regulatory elements for neuron-specific gene expression and (2) reveal adhesion proteins with potential roles in process placement and synaptic specificity. Our expression data are available at https://cengen.org and can be interrogated at the web application CengenApp. We expect that this neuron-specific directory of gene expression will spur investigations of underlying mechanisms that define anatomy, connectivity, and function throughout the C. elegans nervous system.